The Contribution of Renaissance Scholars to the Historiography of Mathematics - Zajíčková, Dagmar (Teorie vědy / Theory of Science, 2013)
review: Robert Goulding. Defending Hypatia: Ramus, Savile and the Renaissance Rediscovery of Mathematical History, New York: Springer, 2010, 201 s.